2022
DOI: 10.1039/d1sc04734e
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating green ammonia manufacture under milder conditions: what do heterogeneous catalyst formulations have to offer?

Abstract: Ammonia production is one of the largest industrial processes, and is currently responsible for over 1.5% of global greenhouse gas emissions. Decarbonising this process, yielding ‘green ammonia’, is critical not...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 120 publications
(154 reference statements)
0
27
0
Order By: Relevance
“…responsible for N 2 activation as well as the subsequent steps of NH 3 synthesis. 16,22 For example, using TM (Mn, Te, or Co) and LiH as active species to catalyze N 2 activation and nitrogen hydrogenation, Chen et al achieved superior activities at low temperature. 23 Over intermetallic LaCoSi, Gong et al observed NH 3 synthesis activity 60-fold that of conventional supported cobalt catalysts, and proposed activated hydrogen on LaCoSi as active species to extract nitrogen from Co sites.…”
mentioning
confidence: 99%
“…responsible for N 2 activation as well as the subsequent steps of NH 3 synthesis. 16,22 For example, using TM (Mn, Te, or Co) and LiH as active species to catalyze N 2 activation and nitrogen hydrogenation, Chen et al achieved superior activities at low temperature. 23 Over intermetallic LaCoSi, Gong et al observed NH 3 synthesis activity 60-fold that of conventional supported cobalt catalysts, and proposed activated hydrogen on LaCoSi as active species to extract nitrogen from Co sites.…”
mentioning
confidence: 99%
“…So, the effect of ambient ammonia contamination is also need to be identified as detail as possible 5,6 . Further advances on novel catalysts design and fundamental understandings regarding the multi-step transfer of electrons and protons during nitrogen hydrogenation are required to overcome limitations of existing nitrogen reduction electrocatalysts such as slow kinetics and high energy barrier [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Further advances on novel catalyst design and fundamental understanding regarding the multi-step transfer of electrons and protons during nitrogen hydrogenation are required to overcome the limitations of existing nitrogen reduction electrocatalysts such as slow kinetics and high energy barrier. [7][8][9][10] Transition metal dichalcogenides with tunable electronic properties have attracted wide attention and have been extensively exploited in electrocatalysis. [11][12][13][14] Of them, inspired by natural metalloenzymes, such as Mo-dependent nitrogenase, MoS 2 exhibits very similar constituent elements and is viewed as a very promising nitrogen functionalization catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…1 Besides decarbonizing the fertilizer industry, a greener pathway for ammonia synthesis will help unlock its use in diverse clean energy transition applications from transportation to gridbalancing. [2][3][4][5] The high pressures and temperatures employed in the HB process make the technology more suited to centralized large-scale operation. 6,7 In contrast, the economic viability and energy efficiency of green ammonia processes, which rely on intermittent renewable energy sources for green hydrogen, would benefit from the use of milder reaction conditions.…”
mentioning
confidence: 99%
“…6,7 In contrast, the economic viability and energy efficiency of green ammonia processes, which rely on intermittent renewable energy sources for green hydrogen, would benefit from the use of milder reaction conditions. 1,5,7 However, conventional HB catalysts are not effective at lower temperatures and pressures, 8,9 motivating the quest for better performing materials under these conditions. [10][11][12] Among the many materials that have recently been investigated for this purpose, alkali and alkaline earth metal-nitrogen-hydrogen systems have shown considerable promise.…”
mentioning
confidence: 99%